PEMAHAMAN KONSEP SISWA DALAM MENYELESAIKAN OPERASI HITUNG PECAHAN KELAS V SDN 03 PONTIANAK KOTA - Yogi Indra; Hamdani Hamdani; Sugiyono Sugiyono (Universitas Tanjungpura, 2019)
AbstractThis study aimed to describe the understanding of students concepts in solving fraction counting operations in fifth grade elementeri school 03 Pontianak Kota. The research method used in this study was descriptive in the from of case study research. The subject in this study were 25 fifth grade elementeri school 03 Pontianak, totaling 25 students.The results of the study showed that the understanding of the concept of upper group students totaling 5 students was high because it could fulfill the first indicator and the second indicator. to understand the concept of the middle group is enough, from 14 students as many as 8 students can meet the first indicator used by researchers that is using, utilizing, and selecting certain procedures or operations and the second indicator is applying the concept to problem solving, while as many as 6 students cannot fulfill indicators used by researchers. while the understanding of the concept of lower group students totaling 6 students is low because it cannot meet the first indicator and the second indicator used by researchers. overall the understanding of students' concepts in solving operational problems in fractions in class V is still low with an average student score of 50.07. Keyword: Fraction , Level of Ability , Understanding of Concepts